Between Efficiency And Traditional Values: Examining Social Sensitivity Of Rural And Urban Communities To The Punjungan Tradition - Larasati, Galuh Lintang; Maulia, Upik; Astri Astuti, Pinky; Sarlotha Modjo, Rehuella; Sari, Lola Purnama (Jurnal Indonesia Sosial Sains, 2025)
The richness of tradition and culture in Javanese society, which is known for its deep values, has undeniably been transformed along with the entry of modernization that changes their social dynamics. This problem occurs in the punjungan tradition in Purworejo Regency, Central Java. The punjungan tradition that is carried out from generation to generation and provides a symbol of nobility for the social life of the community cannot be denied that it must coexist with the modernization of the times. This research aims to identify and analyze the understanding, practice, and social sensitivity of Purworejo people towards the punjungan tradition by comparing responses from rural and urban communities. The research method used is narrative qualitative. Data collection techniques were conducted through interviews, observations, and literature studies, and data analysis was carried out thematically deductively by creating main themes as a reference in the process of data processing, interpretation, and conclusion drawing. At the end of this paper, it provides a conclusion in the form of social sensitivity of rural and urban communities towards the punjungan tradition in an effort to preserve the punjungan tradition in Purworejo Regency.